Associations between morphometric variables and weight and yields carcass in Pirapitinga Piaractus brachypomus. (10th May 2019) - Ribeiro, Fagner Machado; Lima, Mário; Costa, Pedro Aurélio Tataíra da; Pereira, Diego Machado; Carvalho, Thony Assis; de Souza, Tadeu Vilela; Botelho, Hortência Aparecida; Silva, Fabyano Fonseca e; Costa, Adriano Carvalho
Abstract: The objective of this work was to evaluate the association between morphometric variables and carcass characteristics in Pirapitinga. We used a thousand specimens of Pirapitinga with an average weight of 1, 200 g, which were stunned, slaughtered, weighed, measured, and processed for morphometric and processing yield analysis, to obtain weights, carcass and fillet yields. Initially, the linearity of the variables was verified. Pearson's simple and partial correlation tests were performed between all metrics. Track analysis was performed considering the weights and yields of carcass and filet as dependent variables and the others as independent variables. Ridge regression models were used to eliminate the effects of multicollinearity among the independent variables. Observations showed that the simple correlations between body weights and yields were superior to the partial ones in terms of magnitude. The length and circumference of the specimens were the measures most linearly associated with weight, carcass weight and fillet with rib weight. As for carcass yield and fillet yield, linear correlation coefficients were low and not significant when associated with body weights. With the path analysis, we could observe significant positive correlations between the morphometric measurements for weight, carcass weight and fillet with rib weight. The standard length, body circumference and body circumference/body height ratio are the most correlated. The latter are the most important variables in the evaluation of body weights in Pirapitinga fish. They can serve as criteria for indirect selection in searching for fish with better carcass characteristics. As for fillet and carcass yields, the morphometric variables have not shown to be efficient for indirect selection.